If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 3(4x + 8) + -6x = 49 Reorder the terms: 7 + 3(8 + 4x) + -6x = 49 7 + (8 * 3 + 4x * 3) + -6x = 49 7 + (24 + 12x) + -6x = 49 Combine like terms: 7 + 24 = 31 31 + 12x + -6x = 49 Combine like terms: 12x + -6x = 6x 31 + 6x = 49 Solving 31 + 6x = 49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-31' to each side of the equation. 31 + -31 + 6x = 49 + -31 Combine like terms: 31 + -31 = 0 0 + 6x = 49 + -31 6x = 49 + -31 Combine like terms: 49 + -31 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| -X+3=7-X | | 5x+6(-2x+18)=157 | | 2(4x-3)-8=4+sx | | 7x-7-5x=19 | | h=-16t(t-5) | | 2/5-45888/2222 | | C+25=415 | | 7m=(m-4) | | -3(4-a)=-6 | | S=1/5(65-5e) | | 5x-3+3x+45=90 | | 4x-18+90=180 | | y=(x+3)(x^2+25)(x^2-2x+10) | | -3(4-a)=-15 | | -2n-12=-6(2+6n) | | 96=15+9s | | 5x+6(-2+18)=157 | | 5(n+3)=3(2*n-1) | | 8y-3y=35 | | 5x+6(-2+18)=108 | | 4y=3x+C | | 63/w=9 | | 12x=5(8+2x) | | h=-2(t-1)-16t(t-1) | | XP+to=z | | 8m+10=50 | | 4(x-5)+6=2(2x-7) | | x*5+65=4*x | | 24+5h=89 | | 10x-3/12 | | X^2-9x-19/x-2 | | 2x-54=104 |